Comparison of cadaveric and isomorphic three‐dimensional printed models in temporal bone education. (8th August 2015) - Hochman, Jordan B.; Rhodes, Charlotte; Wong, Dana; Kraut, Jay; Pisa, Justyn; Unger, Bertram
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Current three‐dimensional (3D) printed simulations are complicated by insufficient void spaces and inconsistent density. We describe a novel simulation with focus on internal anatomic fidelity and evaluate against template/identical cadaveric education. Study Design Research ethics board‐approved prospective cohort study. Methods Generation of a 3D printed temporal bone was performed using a proprietary algorithm that deconstructs the digital model into slices prior to printing. This supplemental process facilitates removal of residual material from air‐containing spaces and permits requisite infiltrative access to the all regions of the model. Ten otolaryngology trainees dissected a cadaveric temporal bone (CTB) followed by a matched/isomorphic 3D printed bone model (PBM), based on derivative micro‐computed tomography data. Participants rated 1) physical characteristics, 2) specific anatomic constructs, 3) usefulness in skill development, and 4) perceived educational value. The survey instrument employed a seven‐point Likert scale. Results Trainees felt physical characteristics of the PBM were quite similar to CTB, with highly ranked cortical (5.5 ± 1.5) and trabecular (5.2 ± 1.3) bone drill quality. The overall model was considered comparable to CTB (5.9 ± 0.74), with respectable air cell reproduction (6.1 ± 1.1). Internal constructs were rated as satisfactory (range, 4.9–6.2). The simulation was considered a beneficial training tool for all types of mastoidectomy (range, 5.9–6.6), posterior tympanotomy (6.5 ± 0.71), and skull base approaches (range, 6–6.5). Participants believed the model to be an effective training instrument (6.7 ± 0.68), which should be incorporated into the temporal bone lab (7.0 ± 0.0). The PBM was thought to improve confidence (6.7 ± 0.68) and operative performance (6.7 ± 0.48). Conclusions Study participants found the PBM to be an effective platform that compared favorably to CTB. The model was considered a valuable adjunctive training tool with both realistic mechanical and visual character. Level of Evidence NA Laryngoscope, 125:2353–2357, 2015